INDUSTRIAL WELDING: types, applications and technological innovations for more efficient products - Pinheiro, Marco; Reis Filho, Ramilio Ramalho (Revista Interface Tecnológica, 2023)
Welding holds a prominent position in industrial production, serving as a method for joining materials used across various industries, ranging from the crafting of simple grids to the construction of grand transatlantic ships. The most common types of welding encompass electric arc welding, gas welding, friction welding, and laser welding. This technique, frequently employed in manufacturing and restructuring scenarios, stands out due to its numerous advantages. These include its remarkable efficiency in amalgamating parts made from diverse materials, its adaptability to various substances, and the possibility of manual or automated operation, enabling a wide array of actions both on land and underwater. This results in enhanced safety measures, preventing fractures and leaks. Welding technology continues to progress, with ongoing developments of novel materials, equipment, and procedures. Welding, as an invaluable skill, constitutes a critical component of the industrial production process, facilitating the creation of safer, more enduring, and efficient products.